Pelatihan Teknologi Infromasi untuk Meningkatkan Pemahaman Literasi Digital Kepada Masyarakat di Desa Yewena : Penelitian - Axelon S Renyaan; Ermy D Sumanik; Yohan M Indey; Iriani I Bukorpioper (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
community in Yewena village was conducted with the aim of providing basic skills in utilising technology to support daily activities. The training lasted for two days and covered three main topics, namely the use of Microsoft Word, Microsoft Excel, and the Cnva application. To ensure the activity was effective, pre-tests and post-tests were used as measures of success in gauging the improvement in participants' abilities. The approach emphasised direct and communicative interaction with the community, ensuring that the learning process was well received and had a tangible impact. This approach was implemented through mentoring, open dialogue, and relevant practical examples tailored to the community's needs. Mini-studies included in the training covered creating resident letter templates using Microsoft Word, preparing RT cash reports with Microsoft Excel, and creating simple information media using Canva.The training results showed an increase in participants' ability to understand and apply the digital skills provided. Through a contextual approach and hands-on practice, this activity successfully encouraged the Yewena Village community to be more adaptive to technological developments and apply them in their daily lives.